ePortfolio to support professional development during experiential learning placements: Guided by students-as-partners theory, enabled through students-as-partners practice - Roche, Cicely; Abria, Laine; Farrell, Orna; Johnston, Jonathan; Penny Light, Tracy; McKibben, Alexandra; Reast, Aisling; Yancey, Kathleen Blake (International Journal for Students as Partners, 2023)
This case study applies a students-as-partners focus to the use of ePortfolio concepts during experiential learning placements. In describing our project and as evident here, in referring to ePortfolio in the singular, we cite it as an abstract concept, while the plural reference marks practice, in this study taking the form of student-generated instances of ePortfolio use, in particular as detailed in the ePortfolios experiences of two final-year students on experiential placement in a pharmacy programme. These two students used their ePortfolio to document and reflect critically on their experiential placements, showcasing their own student-generated ePortfolios at a symposium co-hosted by student partners, their placement preceptor, and other mentors. This student co-developed case study summarises key findings, including how the use of ePortfolio can support learner agency, and outlines recommendations for further incorporating ePortfolio use in experiential learning contexts. While grounded in the context of an undergraduate pharmacy programme, much of the study will resonate with colleagues based in other disciplines aligned with competency frameworks. The staff-student collaborative approach explored in this case study is likely of interest to students, educators, preceptors, tutors, mentors, and others developing curricula with an ePortfolio component.